Penerapan Disaster Recovery Plan Pada Database MySQL Menggunakan Metode Master to Master Replication Berbasis Docker - Suhatman, Rahmat; Fadhly Rida, Muhammad Arif; Surya, Ibnu; Tasya, Raudatul (Politeknik Caltex Riau, 2024)
Data stored in the database must have protection against attacks and interference. Attacks and disruptions have been experienced by the Caltex Riau Polytechnic (PCR), which only has one database. A database that experiences an attack or disruption results in the information system being inaccessible to users. Currently, PCR does not have an information system recovery plan so that information system recovery will take a long time so that it can be accessed again by users. Therefore, PCR requires a recovery plan if the database experiences an attack or disruption. Based on these problems, this research will create a recovery plan so that the information system can be accessed more quickly when the database experiences an attack or disruption. In this research, database replication was carried out using a Disaster Recovery Plan (DRP) to respond to emergencies, provide backup operations during disruptions, and manage recovery and rescue processes afterwards. The method used is Master to Master MySQL Replication. This method uses 2 servers as master 1 and master 2. If the database on master 1 experiences changes, it will be copied to master 2 in real time. By applying the Master to Master Replication method to the DRP, the PCR information system can provide a directly updated backup for the database, when it experiences an attack or damage